Pengaruh Periklanan, Harga dan Kualitas Produk Terhadap Keputusan Pembelian dengan Minat Beli Sebagai Variabel Intervening pada Produk Kopi Kenangan di Mangunjaya (Studi Kajian Pustaka) - EHJ. FoEh, John; Damayanti, Allya (Dinasti Review Publisher, 2023)
This study aims to find out the description of advertising, price, and product quality on purchasing decisions through buying interest which is the intervening variable for Kopi Kenangan products in Mangunjaya, Bekasi Regency. The method in this study is quantitative. The primary data in this study is primary data using a questionnaire. The sampling method in this study used the accidental sampling technique. The population in this study are people who come to Kopi Kenangan in Mangunjaya to buy. The sample in this study amounted to 233 respondents. The analysis in this study uses SEM analysis with data processing using SPSS 25 and SmartPLS. The results of this study show that when advertising, price, and product quality influence purchase intention, advertising variables, price, and product quality influence purchasing decisions. Advertising and product quality influence purchase decisions through purchase intention. Prices without influencing purchasing decisions through buying interest in Kopi Kenangan products in Mangunjaya.